Conductive silver paste for tin soldering of electronic component and preparation method of conductive silver paste

By using conductive silver paste prepared by raw materials such as nano silver powder, polyurethane prepolymer, functionalized graphene and silver copper powder in tin soldering of electronic components, the problem of insufficient conductivity and adhesion performance in the prior art is solved, and higher conductivity, adhesion and stability are achieved.

CN119811740AActive Publication Date: 2025-04-11SHENZHEN JIANHE SMART CARD TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411701551.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-04-11
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The existing conductive silver paste has insufficient adhesion and conductivity in tin soldering of electronic components, making it difficult to meet the high requirements of tin soldering applications.

Method used

A conductive silver paste is prepared by using nano silver powder, polyurethane prepolymer, functionalized graphene and silver copper powder. The method includes pretreating the nanosilver powder, forming a cladding layer to prevent agglomeration, and improving conductivity and adhesion through the addition of functionalized graphene and polyurethane prepolymers.

Benefits of technology

It significantly improves the conductivity, adhesion and stability of the conductive silver paste, reduces resistance, enhances oxidation resistance and corrosion resistance, extends service life, and improves the bonding force with the matrix material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119811740A_ABST
    Figure CN119811740A_ABST
Patent Text Reader

Abstract

The invention discloses conductive silver paste for tin soldering of an electronic element and a preparation method of the conductive silver paste, and relates to the technical field of conductive silver paste. According to the conductive silver paste for tin soldering of the electronic element and the preparation method of the conductive silver paste, the nano silver powder is pretreated through the organic acid, so that carboxyl in the organic acid interacts with the surface of the nano silver powder to form a coating layer, silver powder agglomeration is prevented, the silver powder is uniformly dispersed in the paste, the stability of the paste is improved, and the resistance is reduced; the treated nano silver powder is more tightly contacted with each other to form a good conductive network, so that the conductivity of the conductive paste is improved; and in the air, the nano silver powder is easily oxidized, and a protective film is formed on the surface of the silver powder through the organic acid, so that oxygen and moisture are blocked, the oxidation speed of the silver powder is reduced, the oxidation resistance of the paste is improved, and the service life is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of conductive silver paste, in particular to a conductive silver paste for tin welding of electronic components and a preparation method thereof. Background Art

[0002] The Chinese patent with publication number CN118398278A discloses a conductive silver paste and a method for preparing the conductive silver paste. The method for preparing the conductive silver paste comprises the following steps: S1: preparing a reducing solution; S2: preparing an oxidizing solution; S3: preparing a neutralizing solution; S4: performing an oxidation-reduction reaction to obtain a silver-containing solution; S5: post-treating the silver-containing solution; S6: preparing a conductive silver paste; the application can prepare a conductive silver paste with a lower square resistance, and the preparation method is simple, easy to repeat, and the result is stable. However, the adhesion performance and the conductivity of the conductive silver paste prepared by the above-mentioned prior art scheme need to be further improved; for this reason, the present invention provides a conductive silver paste for tin soldering of electronic components and a preparation method thereof to solve the above-mentioned problems. Summary of the invention

[0003] In view of the deficiencies in the prior art, the present invention provides a conductive silver paste for tin soldering of electronic components and a preparation method thereof, which solves the problems mentioned in the above background technology.

[0004] To achieve the above objectives, the present invention is implemented through the following technical scheme: a conductive silver paste for tin soldering of electronic components, comprising the following raw materials in parts by weight: 60-85 parts of nano silver powder, 2-5 parts of polyurethane prepolymer, 0.8-2 parts of functionalized graphene, and 8-10 parts of silver copper powder.

[0005] A method for preparing conductive silver paste for tin soldering of electronic components, specifically comprising the following preparation steps:

[0006] Step 1, pre-treating the nano silver powder: pouring malonic acid, adipic acid, sebacic acid and oleic acid into ethanol to dissolve, preparing an organic acid ethanol solution with a concentration of 0.50-0.70 mol / L, then pouring 10-15 g of nano silver powder into 180-200 mL of the organic acid ethanol solution, ultrasonically treating for 1.5-2 h, standing for 4-6 h and then filtering, then washing with ethanol 2-3 times, and finally placing in a vacuum oven at room temperature to dry for 42-48 h;

[0007] Step 2: Add silver copper powder, polyurethane prepolymer and functionalized graphene to the pretreated nano silver powder in sequence, mix and grind to obtain a mixture, and degas the mixture to obtain a conductive silver paste.

[0008] Preferably, the preparation method of the nano silver powder is:

[0009] S1. Dissolve 5.2-6.5 g of silver nitrate in 36-40 mL of deionized water. Heat the water bath to 45-55° C. under stirring.

[0010] S2, dropwise add the solution in S1 to 0.7-1.8 g of reducing agent, after completion of dropwise addition, stir for 25-30 min, and then ultrasonically treat at a speed of 1000-3000 r / min for 15-20 min;

[0011] S3, dropwise add 5% ammonia solution, adjust the pH value of the mixed solution to 5-7, and then stir for 25-30 minutes;

[0012] S4, soaking in a 1% by mass 1,2,3-benzotriazole aqueous solution for 20-25 minutes and then filtering;

[0013] S5. Wash with deionized water for 3-5 times, then wash with anhydrous ethanol and acetone for 1-2 times respectively, and finally dry and grind in a vacuum drying oven at 50-60° C. to obtain nano silver powder.

[0014] Preferably, in step 2, the reducing agent is prepared by dissolving 2.4-2.8 g of sodium hypophosphite, 0.8-1.2 g of sodium hexametaphosphate, 6.3-6.5 g of polyvinyl pyrrolidone and 2.5-4 mL of 1 mol / L dilute sulfuric acid in 235-250 mL of deionized water, stirring evenly to obtain the reducing agent.

[0015] Preferably, the preparation method of the functionalized graphene is:

[0016] (1) Mix 1.5-3 g of ethylenediamine with 2-6 g of graphene dispersion and perform ultrasonic treatment for 20-30 min;

[0017] (2) adding 20-35 mL of methanol, and then slowly adding 0.8-1.5 g of methyl acrylate, and stirring the reaction under nitrogen atmosphere for 22-24 hours;

[0018] (3) After the reaction is completed, pour into 20-35 mL of methanol, wait for complete dissolution, slowly add 0.8-1.5 g of ethylenediamine, and stir the reaction under nitrogen atmosphere for 22-24 hours to obtain functionalized graphene.

[0019] Preferably, the preparation method of the graphene dispersion is: 15-25g of graphite is mixed with 150-165mL of acetonitrile, and then 2.5-4g of 1-cyanoethyl-2-ethyl-4-methylimidazole is added, and after mixing, ultrasonic dispersion treatment is performed for 2.5-3h, and then the dispersion is taken out and allowed to stand for 20-24h, the upper layer liquid is taken out, and centrifuged at a speed of 3500-4000r / min for 20-30min to obtain the graphene dispersion.

[0020] Preferably, the synthesis method of the polyurethane prepolymer is:

[0021] Ⅰ. Dissolve 16-25 g of diisocyanate in 23-34 mL of toluene;

[0022] Ⅱ. Under nitrogen atmosphere, pour 5.5-8g of polyester diol into 45-50mL of toluene for dissolution, add 1.2-2.5g of dibutyltin dilaurate, heat the oil bath to 40℃ and stir to react;

[0023] III. Dissolve 4.3-4.8 g of methyl ethyl ketone oxime in 10 mL of toluene, then pour into the mixed solution in Ⅱ, heat to 50-60°C, react for 1.5-2h, and distill under reduced pressure at 65-70°C.

[0024] Preferably, the diisocyanate is selected from one of toluene diisocyanate, isophorone diisocyanate and 1,4-toluene diisocyanate; and the polyester diol is selected from one of polyethylene glycol, polypropylene glycol, polytetramethylene glycol and polycarbonate diol.

[0025] Beneficial Effects

[0026] The present invention provides a conductive silver paste for tin soldering of electronic components and a preparation method thereof. Compared with the prior art, it has the following beneficial effects:

[0027] (1) The conductive silver paste for tin soldering of electronic components and its preparation method are as follows: nano silver powder is pretreated by organic acid, so that the carboxyl group in the organic acid interacts with the surface of the nano silver powder to form a coating layer, thereby preventing the silver powder from agglomerating and making it uniformly dispersed in the paste, improving the stability of the paste, reducing the resistance, and the treated nano silver powders are in closer contact with each other to form a good conductive network, thereby improving the conductive performance of the conductive paste; and in the air, the nano silver powder is easily oxidized, and the organic acid forms a protective film on the surface of the silver powder to block oxygen and moisture, reduce the oxidation rate of the silver powder, improve the antioxidant capacity of the paste, and extend the service life; the organic acid can also improve the compatibility and affinity between the nano silver powder and the matrix material, so that the silver powder is better attached to the surface of the matrix, enhance the bonding force between the conductive paste and the matrix, and prevent the silver powder from falling off or the conductive layer from peeling off due to external force during use.

[0028] (2) The conductive silver paste for tin soldering of electronic components and its preparation method, through the addition of functionalized graphene, have the following effects: 1. It can work synergistically with silver powder to form a more complete conductive network, improve the conductive properties of the conductive silver paste, make current transmission smoother, and reduce resistance; 2. It can be adsorbed on the surface of silver powder to play the role of a dispersant, further prevent the silver powder from agglomerating, improve the stability and consistency of the paste, and ensure the stability of the conductive properties; 3. It can enhance the bonding force between the conductive silver paste and the base material, improve the adhesion and mechanical strength of the coating, and prevent the silver powder from falling off or the conductive layer from peeling off during use; 4. It can form a protective film on the surface of the silver powder to block the contact between moisture, oxygen and other corrosive substances in the external environment and the silver powder, reduce the rate at which the silver powder is oxidized or corroded, and improve the corrosion resistance and service life of the conductive silver paste.

[0029] (3) The conductive silver paste for tin soldering of electronic components and its preparation method can effectively improve the bonding force between silver powder and substrate by adding polyurethane prepolymer, so that the conductive silver paste can be firmly attached to the surface of various materials after curing, preventing the silver paste from falling off due to external force during use, thereby ensuring the stability of the conductive path; it can also make the conductive silver paste have a certain elasticity and flexibility after curing, so that it can adapt to substrates of different shapes and curves, reducing the cracking or failure of the conductive silver paste due to deformation of the substrate; at the same time, it can undergo cross-linking reaction with other active groups to form a stable three-dimensional network structure, thereby improving the heat resistance, water resistance and chemical corrosion resistance of the conductive silver paste.

[0030] (4) The conductive silver paste for tin soldering of electronic components and its preparation method form a protective film on the surface of silver powder through 1,2,3-benzotriazole to prevent the silver powder from being oxidized and enhance the stability of the silver powder, thereby maintaining the long-term stability of the conductive properties of the conductive silver paste; and during the reaction process, substances such as sodium hypophosphite, sodium hexametaphosphate, and polyvinyl pyrrolidone can improve the dispersibility of the silver powder, form a more uniform conductive network, and at the same time improve the adhesion between the silver powder and the base material. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a comparison chart of the water contact angle test provided by the present invention. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Example 1

[0034] A method for preparing conductive silver paste for tin soldering of electronic components, specifically comprising the following preparation steps:

[0035] Step 1, preparation of nano silver powder: dissolve 5.2g of silver nitrate in 36mL of deionized water, and heat the water bath to 45°C under stirring; add the above solution dropwise to 0.7g of reducing agent, stir for 25min after the addition is completed, and then ultrasonically treat at a speed of 1000r / min for 15min; add a 5% ammonia solution by mass fraction, adjust the pH value of the mixed solution to 5, and then stir for 25min; soak in a 1% 1,2,3-benzotriazole aqueous solution by mass fraction for 20min and then filter; wash with deionized water 3 times, then wash with anhydrous ethanol and acetone once respectively, and finally dry and grind in a vacuum drying oven at 50°C to obtain nano silver powder;

[0036] Step 2, pre-treating the nano silver powder: pouring malonic acid, adipic acid, sebacic acid and oleic acid into ethanol to dissolve, preparing an organic acid ethanol solution with a concentration of 0.50 mol / L, then pouring 10 g of nano silver powder into 180 mL of the organic acid ethanol solution, ultrasonically treating for 1.5 h, standing for 4 h and then filtering, then washing with ethanol twice, and finally drying in a vacuum oven at room temperature for 42 h;

[0037] Step 3, preparation of polyurethane prepolymer: 16g of toluene diisocyanate was dissolved in 23mL of toluene; under the protection of nitrogen atmosphere, 5.5g of polyethylene glycol was poured into 45mL of toluene for dissolution, and 1.2g of dibutyltin dilaurate was added, and the oil bath was heated to 40°C and stirred for reaction to obtain solution A; 4.3g of methyl ethyl ketone oxime was dissolved in 10mL of toluene, and then poured into solution A, heated to 50°C, reacted for 1.5h, and distilled under reduced pressure at 65°C;

[0038] Step 4: Preparation of functionalized graphene:

[0039] (1) 15 g of graphite was mixed with 150 mL of acetonitrile, and then 2.5 g of 1-cyanoethyl-2-ethyl-4-methylimidazole was added. After mixing, the dispersion was subjected to ultrasonic dispersion treatment for 2.5 h. The dispersion was then taken out and allowed to stand for 20 h. The upper layer was taken out and centrifuged at 3500 r / min for 20 min to obtain a graphene dispersion.

[0040] (2) 2 g of graphene dispersion was mixed with 1.5 g of ethylenediamine and subjected to ultrasonic treatment for 20 min; 20 mL of methanol was added, and then 0.8 g of methyl acrylate was slowly added dropwise, and the mixture was stirred for 22 h under a nitrogen atmosphere; after the reaction was completed, the mixture was poured into 20 mL of methanol, and after the mixture was completely dissolved, 0.8 g of ethylenediamine was slowly added dropwise, and the mixture was stirred for 22 h under a nitrogen atmosphere to obtain functionalized graphene;

[0041] Step 5: Take 60 g of the pretreated nano silver powder, add 8 g of silver copper powder, 2 g of polyurethane prepolymer and 0.8 g of functionalized graphene thereto in sequence, mix and grind to obtain a mixture, and degas the mixture to obtain a conductive silver paste.

[0042] Example 2

[0043] A method for preparing conductive silver paste for tin soldering of electronic components, specifically comprising the following preparation steps:

[0044] Step 1, preparation of nano silver powder: dissolve 6.1g of silver nitrate in 38mL of deionized water, and heat the water bath to 50°C under stirring; add the above solution dropwise to 1.2g of reducing agent, stir for 27min after the addition is completed, and then ultrasonically treat at a speed of 2000r / min for 17min; add a 5% ammonia solution by mass fraction, adjust the pH value of the mixed solution to 6, and then stir for 28min; soak in a 1% 1,2,3-benzotriazole aqueous solution by mass fraction for 23min and then filter; wash with deionized water 4 times, then wash with anhydrous ethanol and acetone twice respectively, and finally dry and grind in a vacuum drying oven at 55°C to obtain nano silver powder;

[0045] Step 2, pre-treating the nano silver powder: pouring malonic acid, adipic acid, sebacic acid and oleic acid into ethanol to dissolve, preparing an organic acid ethanol solution with a concentration of 0.60 mol / L, then pouring 12 g of nano silver powder into 190 mL of the organic acid ethanol solution, ultrasonically treating for 1.6 h, standing for 5 h and then filtering, then washing with ethanol 3 times, and finally drying in a vacuum oven at room temperature for 45 h;

[0046] Step 3, preparation of polyurethane prepolymer: 21g of isophorone diisocyanate was dissolved in 28mL of toluene; under the protection of nitrogen atmosphere, 6.5g of polypropylene glycol was poured into 48mL of toluene for dissolution, and 1.9g of dibutyltin dilaurate was added, and the oil bath was heated to 40°C and stirred for reaction to obtain solution A; 4.5g of methyl ethyl ketone oxime was dissolved in 10mL of toluene, and then poured into solution A, heated to 55°C, reacted for 1.8h, and distilled under reduced pressure at 68°C;

[0047] Step 4: Preparation of functionalized graphene:

[0048] (1) 20 g of graphite was mixed with 160 mL of acetonitrile, and then 3.2 g of 1-cyanoethyl-2-ethyl-4-methylimidazole was added. After mixing, the dispersion was subjected to ultrasonic dispersion treatment for 2.8 h. The dispersion was then taken out and allowed to stand for 22 h. The upper layer was taken out and centrifuged at 3800 r / min for 25 min to obtain a graphene dispersion.

[0049] (2) 4 g of graphene dispersion was mixed with 2.2 g of ethylenediamine and subjected to ultrasonic treatment for 25 min; 25 mL of methanol was added, and then 1.2 g of methyl acrylate was slowly added dropwise, and the mixture was stirred for 23 h under a nitrogen atmosphere; after the reaction was completed, the mixture was poured into 28 mL of methanol, and after the mixture was completely dissolved, 1.1 g of ethylenediamine was slowly added dropwise, and the mixture was stirred for 23 h under a nitrogen atmosphere to obtain functionalized graphene;

[0050] Step 5: Take 75 g of the pretreated nano-silver powder, add 9 g of silver-copper powder, 3.5 g of polyurethane prepolymer and 1.4 g of functionalized graphene thereto in sequence, mix and grind to obtain a mixture, and degas the mixture to obtain a conductive silver paste.

[0051] Example 3

[0052] A method for preparing conductive silver paste for tin soldering of electronic components, specifically comprising the following preparation steps:

[0053] Step 1, preparation of nano silver powder: dissolve 6.5g of silver nitrate in 40mL of deionized water, and heat the water bath to 55°C under stirring; add the above solution dropwise to 1.8g of reducing agent, stir for 30min after the addition is completed, and then ultrasonically treat at a speed of 3000r / min for 20min; add a 5% ammonia solution by mass fraction, adjust the pH value of the mixed solution to 7, and then stir for 30min; soak in a 1% 1,2,3-benzotriazole aqueous solution by mass fraction for 25min and then filter; wash with deionized water for 5 times, then wash with anhydrous ethanol and acetone for 2 times respectively, and finally dry and grind in a vacuum drying oven at 60°C to obtain nano silver powder;

[0054] Step 2, pre-treating the nano silver powder: pouring malonic acid, adipic acid, sebacic acid and oleic acid into ethanol to dissolve, preparing an organic acid ethanol solution with a concentration of 0.70 mol / L, then pouring 15 g of nano silver powder into 200 mL of the organic acid ethanol solution, ultrasonically treating for 2 h, standing for 6 h and then filtering, then washing with ethanol 3 times, and finally drying in a vacuum oven at room temperature for 48 h;

[0055] Step 3, preparation of polyurethane prepolymer: 25g of 1,4-toluene diisocyanate was dissolved in 34mL of toluene; under the protection of nitrogen atmosphere, 8g of polytetrahydrofuran diol was poured into 50mL of toluene for dissolution, and 2.5g of dibutyltin dilaurate was added, and the oil bath was heated to 40°C and stirred for reaction to obtain solution A; 4.8g of methyl ethyl ketone oxime was dissolved in 10mL of toluene, and then poured into solution A, heated to 60°C, reacted for 2h, and distilled under reduced pressure at 70°C;

[0056] Step 4: Preparation of functionalized graphene:

[0057] (1) 25 g of graphite was mixed with 165 mL of acetonitrile, and then 4 g of 1-cyanoethyl-2-ethyl-4-methylimidazole was added. After mixing, the dispersion was ultrasonically dispersed for 3 h, and then the dispersion was taken out and allowed to stand for 24 h. The upper layer was taken out and centrifuged at 4000 r / min for 30 min to obtain a graphene dispersion;

[0058] (2) 6 g of graphene dispersion was mixed with 3 g of ethylenediamine and subjected to ultrasonic treatment for 30 min; 35 mL of methanol was added, and then 1.5 g of methyl acrylate was slowly added dropwise, and the mixture was stirred for 24 h under a nitrogen atmosphere; after the reaction was completed, the mixture was poured into 35 mL of methanol, and after the mixture was completely dissolved, 1.5 g of ethylenediamine was slowly added dropwise, and the mixture was stirred for 24 h under a nitrogen atmosphere to obtain functionalized graphene;

[0059] Step 5: Take 85 g of the pretreated nano-silver powder, add 10 g of silver-copper powder, 5 g of polyurethane prepolymer and 2 g of functionalized graphene thereto in sequence, mix and grind to obtain a mixture, and degas the mixture to obtain a conductive silver paste.

[0060] Comparative Example 1

[0061] Compared with Example 1, the difference is that the nano silver powder in Example 1 is not pretreated.

[0062] Comparative Example 2

[0063] Compared with Example 1, the difference is that the functionalized graphene in Example 1 is replaced by graphene.

[0064] Comparative Example 3

[0065] Compared with Example 1, the difference is that the synthesis method of the polyurethane prepolymer in Example 1 is replaced: 5.5 g of polyethylene glycol is added dropwise to 16 g of toluene diisocyanate, the reaction temperature is 40°C, and the reaction is continued for 1.5 hours after the addition is completed. Then the temperature is raised to 60°C, and hydroxyethyl methacrylate dissolved with 1.2 g of dibutyltin dilaurate is added, wherein the mass of hydroxyethyl methacrylate is 1.2 g.

[0066] Comparative Example 4

[0067] Compared with Example 1, the difference is that the nano silver powder in Example 1 is replaced by silver powder, and no pretreatment is performed.

[0068] Bending resistance test: bend the printed conductor 180° outward symmetrically, and use a weight to press on the silver paste with a pressure of about 5.5kPa, and keep it for 1 minute; then fold the printed conductor 180° in the opposite direction, use the same weight to press on the silver paste, and keep it for 1 minute to test the conductivity of the silver paste. The above steps are regarded as one bending test, and the above operations are repeated until the wire is broken (test times <10 times).

[0069] Resistivity and conductivity test: First, the prepared silver paste was coated on a glass slide to obtain a conductive circuit with a length of 25 mm, a width of 10 mm, and a thickness of about 50 um. The size of the circuit was controlled by a polyimide tape fixed on the glass substrate. Then, the coated silver paste was vacuum cured at 120°C for 2 h. Finally, the RTS-9 dual-electrical four-probe tester was used for detection. The results are shown in Table 1.

[0070] Adhesion test: The test was conducted in accordance with GB9286-98, where 5B is the best 100-grid test level and 0B is the worst 100-grid test level; the results are shown in Table 1.

[0071] Pencil hardness test: The test was conducted in accordance with GB / T6739-2006; the results are shown in Table 1.

[0072] Table 1

[0073]

[0074] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.

[0075] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0076] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A conductive silver paste for soldering electronic components, characterized in that: The invention comprises the following raw materials in parts by weight: 60-85 parts of nano silver powder, 2-5 parts of polyurethane prepolymer, 0.8-2 parts of functionalized graphene and 8-10 parts of silver copper powder.

2. A method for preparing a conductive silver paste for soldering electronic components according to claim 1, characterized in that: The specific preparation steps include the following: Step 1, pre-treating the nano silver powder: pouring malonic acid, adipic acid, sebacic acid and oleic acid into ethanol to dissolve, preparing an organic acid ethanol solution with a concentration of 0.50-0.70 mol / L, then pouring 10-15 g of nano silver powder into 180-200 mL of the organic acid ethanol solution, ultrasonically treating for 1.5-2 h, standing for 4-6 h and then filtering, then washing with ethanol 2-3 times, and finally placing in a vacuum oven at room temperature to dry for 42-48 h; Step 2: Add silver copper powder, polyurethane prepolymer and functionalized graphene to the pretreated nano silver powder in sequence, mix and grind to obtain a mixture, and degas the mixture to obtain a conductive silver paste.

3. The method for preparing a conductive silver paste for soldering electronic components according to claim 2, characterized in that: The preparation method of the nano silver powder is: S1. Dissolve 5.2-6.5 g of silver nitrate in 36-40 mL of deionized water. Heat the water bath to 45-55° C. under stirring. S2, dropwise add the solution in S1 to 0.7-1.8 g of reducing agent, after the dropwise addition is completed, stir for 25-30 min, and then ultrasonically treat at a speed of 1000-3000 r / min for 15-20 min; S3, dropwise add 5% ammonia solution, adjust the pH value of the mixed solution to 5-7, and then stir for 25-30 minutes; S4, soaking in a 1% by mass 1,2,3-benzotriazole aqueous solution for 20-25 minutes and then filtering; S5. Wash with deionized water for 3-5 times, then wash with anhydrous ethanol and acetone for 1-2 times respectively, and finally dry and grind in a vacuum drying oven at 50-60° C. to obtain nano silver powder.

4. The conductive silver paste for soldering electronic components and the preparation method thereof according to claim 3, characterized in that: In the step 2, the reducing agent is prepared by dissolving 2.4-2.8 g of sodium hypophosphite, 0.8-1.2 g of sodium hexametaphosphate, 6.3-6.5 g of polyvinyl pyrrolidone and 2.5-4 mL of 1 mol / L dilute sulfuric acid in 235-250 mL of deionized water, and stirring evenly to obtain the reducing agent.

5. The conductive silver paste for soldering electronic components and the preparation method thereof according to claim 2, characterized in that: The preparation method of the functionalized graphene is: (1) Mix 1.5-3 g of ethylenediamine with 2-6 g of graphene dispersion and perform ultrasonic treatment for 20-30 min; (2) adding 20-35 mL of methanol, and then slowly adding 0.8-1.5 g of methyl acrylate, and stirring the reaction under nitrogen atmosphere for 22-24 hours; (3) After the reaction is completed, pour into 20-35 mL of methanol, wait for complete dissolution, slowly add 0.8-1.5 g of ethylenediamine, and stir the reaction under nitrogen atmosphere for 22-24 hours to obtain functionalized graphene.

6. The conductive silver paste for soldering electronic components and the preparation method thereof according to claim 5, characterized in that: The preparation method of the graphene dispersion liquid is as follows: 15-25 g of graphite is mixed with 150-165 mL of acetonitrile, and then 2.5-4 g of 1-cyanoethyl-2-ethyl-4-methylimidazole is added, and after mixing, ultrasonic dispersion treatment is performed for 2.5-3 hours, and then the dispersion liquid is taken out and allowed to stand for 20-24 hours, and the upper layer liquid is taken out, and centrifuged at a speed of 3500-4000 r / min for 20-30 minutes to obtain the graphene dispersion liquid.

7. The conductive silver paste for soldering electronic components and the preparation method thereof according to claim 2, characterized in that: The synthesis method of the polyurethane prepolymer is: Ⅰ. Dissolve 16-25 g of diisocyanate in 23-34 mL of toluene; Ⅱ. Under nitrogen atmosphere, pour 5.5-8g of polyester diol into 45-50mL of toluene for dissolution, add 1.2-2.5g of dibutyltin dilaurate, heat the oil bath to 40℃ and stir to react; III. Dissolve 4.3-4.8 g of methyl ethyl ketone oxime in 10 mL of toluene, then pour into the mixed solution in Ⅱ, heat to 50-60°C, react for 1.5-2h, and distill under reduced pressure at 65-70°C.

8. The conductive silver paste for soldering electronic components and the preparation method thereof according to claim 7, characterized in that: The diisocyanate is selected from one of toluene diisocyanate, isophorone diisocyanate and 1,4-toluene diisocyanate; the polyester diol is selected from one of polyethylene glycol, polypropylene glycol, polytetramethylene glycol and polycarbonate diol.

Citation Information

Patent Citations

  • Conductive silver paste and preparation method thereof

    CN118398278A

  • Method for preparing polyamide-amine in-situ intercalation graphene composite material

    CN102390830A

  • Nano-silver coated copper powder lower-temperature sintering solder paste and preparation method thereof

    CN103521945A

  • Composite conductive silver paste and preparation method thereof

    CN109887640A

  • Graphene-doped conductive silver paste

    CN112694791A